VOLTAMMETRIC/ POLAROGRAPHY TRACE METAL ANALYZER AND ITS FORENSIC APPLICATION- A REVIEW (Journal of Forensic Medicine & Toxicology, 2013)
Voltammetry and Polarography belongs to the group of traditional electroanalytical methods, which has been successfully used for almost ninety years for different analysis for environmental as well as biological samples. This technique has achieved many pronounced success in determination of trace elements due to high sensitivity, preciseness, simple managing and ability of speciation. However, number of voltammetric devices has decreased in course of last decade. An attempt has been made to introduce an analytical technique based on polarographic and voltammetry. Trace metal analyzer plays an important role in the determination of heavy metals and other harmful substances at ppb and ppt levels for a wide range of samples. One of cheapest way to perform the analysis of large varieties of heavy metal ions is to use electrochemical methods and the most sensitive are stripping voltammetric methods. Analysis of heavy metals using voltammetric methods are highly advantageous due to the compact size of the instrument allowing potential portability and low cost as compared to the other techniques. This paper is in continuation of Forensic Instrumental technique series, Article VII, Microwave digester and its Forencsic Application- A review, Journal of Forensic Medicine and Toxicology Vol 28, No 1, Jan June 2011.
Keywords: ICP-MS; Polarography; Voltammetry; ASV; CSV; AdSV; Trace Metal Analyzer etc